Research on improving situation awareness of individals and the Singapore civil defence force personnel - Ho, Terence Chee Wah. (2011)
There have been numerous cases of fire break outs in Singapore. Many a times, one or two victims will perish during this disaster. In order to minimize such unfortunate cases, this research examines how situation awareness of individuals can be increased, be it civilians or the Singapore Civil Defense Force (SCDF).